2018
DOI: 10.3389/fpls.2018.00087
|View full text |Cite
|
Sign up to set email alerts
|

Approaches and Recent Developments for the Commercial Production of Semi-synthetic Artemisinin

Abstract: The antimalarial drug artemisinin is a natural product produced by the plant Artemisia annua. Extracts of A. annua have been used in Chinese herbal medicine for over two millennia. Following the re-discovery of A. annua extract as an effective antimalarial, and the isolation and structural elucidation of artemisinin as the active agent, it was recommended as the first-line treatment for uncomplicated malaria in combination with another effective antimalarial drug (Artemisinin Combination Therapy) by the World … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 48 publications
0
52
0
1
Order By: Relevance
“…Several CYPs and engineered variants are now used to synthesize and produce various compounds on a larger scale and for diverse purposes, including drug discovery and development [1]. For instance, artemisinic acid, a precursor for the Artemisia annua-derived antimalarial drug, artemisinin, has been synthesized using an engineered form of the plant's CYP71AV1 enzyme [103]. Furthermore, engineered CYPs have utility in statin synthesis.…”
Section: Use Of Ev Cyps In Synthetic Biologymentioning
confidence: 99%
“…Several CYPs and engineered variants are now used to synthesize and produce various compounds on a larger scale and for diverse purposes, including drug discovery and development [1]. For instance, artemisinic acid, a precursor for the Artemisia annua-derived antimalarial drug, artemisinin, has been synthesized using an engineered form of the plant's CYP71AV1 enzyme [103]. Furthermore, engineered CYPs have utility in statin synthesis.…”
Section: Use Of Ev Cyps In Synthetic Biologymentioning
confidence: 99%
“…This question was answered with a second paper from the group, applying the method to the popular example of the anti‐malarial drug artemisinin ( 43 ) . P450 enzymes are involved in artemisinin's biosynthesis and thus semi‐synthetic supply is applicable,, which is managed through methods of metabolic engineering and synthetic biology ,. Late‐stage diversification of the drug can be achieved through synthetic chemistry tools used to synthesise new analogues or metabolic products,, often with aid of organometallic catalysis ,…”
Section: Examplesmentioning
confidence: 99%
“…However, in 2016 it was reported that Sanofi would not proceed with production and was selling its production facility [73]. At the time of writing recent reports suggest that production is under way and that more efficient routes to semi-synthetic synthesis have been identified [74].…”
Section: Panel 3 Inmentioning
confidence: 99%